PERANCANGAN BUSANA READY-TO-WEAR DELUXE WANITA DENGAN KONSEP KESETARAAN GENDER MENGGUNAKAN SURFACE DESIGN EMBROIDERY - Soehartono, Sharren; Enrico, Enrico; Githapradana, Dewa Made Weda (MODA, 2025)
Different perspectives and ways of thinking about culture and beliefs can be a source of gender issues in society. According to historical records, most societies in the past still adhere to a patriarchal culture, which places men as the main power holder and treats women as weak people who have no power. Some communities still adhere to this culture today. This research aims to represent gender equality and women empowerment through the design of women's deluxe ready-to-wear clothing using surface design embroidery. The qualitative research method was conducted by interviewing 6 fashion experts and 12 extreme users, as well as journals, news, and online observations as secondary data collection. The design method used is the design thinking method with the stages of empathize, define, ideate, prototype, to test, which is a guide so that the design results are in accordance with the initial concept. The result of this design consisted of 5 sets of deluxe ready-to-wear clothing that combined structure, feminine, and revealing elements with the main materials of semi wool, tweed, and chiffon and the application of surface design embroidery exploration with an unfinished impression to convey gender equality and women empowerment issues. This collection is aimed at women fashion enthusiasts aged 20 - 35 who value uniqueness and quality, prioritize trend and style, and have middle to upper class status. Through the application of surface design embroidery on clothing, it is hoped that it can be a solution in building public awareness about gender equality and women empowerment.